Naming and Mapping the Gods in the Ancient Mediterranean (De Gruyter, 2023)
Gods dwell in human environments in multiple ways. They move into imaginary spaces and explore the cosmos. This book analyzes the mapping of gods through a specific lens: their naming. By proposing this new perspective, it sheds light on ritual practices and representations of gods in the whole Mediterranean, from Italy to Mesopotamia, from Greece to North Africa and Egypt. Names and spaces enable to better define, differentiate, and connect gods.